PREVALENCE OF NASAL POLYPS IN CHRONIC RHINOSINUSITIS PATIENTS UNDERGOING FUNCTIONAL ENDOSCOPIC SINUS SURGERY - Abdul Azeem Rasouli (Interdisciplinary Approaches to Medicine, 2021)
Chronic Rhinosinusitis (CRS) is a common disease that affects a large percentage of the population, Nasal obstruction, nasal discharge, headache and the decline in quality of life are all symptoms that have social and economic consequences. CRS with nasal polyps is a common problem, it is a subgroup of CRS in which polyps in the middle meatus can be seen. It has a high social impact because of its chronic disease burden. Due to a large number of people with medically refractory rhinosinusitis, it is now widely accepted to use functional endoscopic sinus surgery (FESS) and the number of FESS procedures that are performed has increased. The study aimed to assess nasal polyps in chronic rhinosinusitis patients who underwent FESS. A retrospective study was conducted among patients aged between 18 and 86 years. The clinical records of patients who underwent functional endoscopic sinus surgery over the two years (2019-2020) were carefully reviewed and pertinent information was extracted from the database. Overall, 1671 patients underwent FESS, 1197 of them were for CRS. We found 165 (13.78%) patients with nasal polyps and 1032 (86.21%) of them were without nasal polyps. The study group’s mean age was 38.87±14.74 years. The mean age of patients for CRS with nasal polyps and without nasal polyps was 50.53±16.13 and 37±13.61 years respectively, which was statically significant (χ2 =216.303; p < 0.001). Most of the patients with nasal polyps (43%) were aged between 41-60 years. In the subgroup of CRS with nasal polyp females and males were 79 (47.88%) and 86 (52.12%) respectively. In our study, both CRS with nasal polyps and without nasal polyps showed significant age differences. In CRS with nasal polyp, males were more affected than females. More research is needed to assess demographic variables and outcomes of nasal polyps after FESS.